Theoretical Study on the Structural-Function Relationship of Manganese(III)-Iodosylarene Adducts - Sun, Dongru; Chen, Xiaolu; Gao, Lanping; Zhao, Yufen; Wang, Yong (Frontiers in Chemistry, 2020)
Metal-iodosylarene complexes have been recently viewed as a second oxidant alongside of the well-known high-valent metal-oxo species. Extensive efforts have been exerted to unveil the structure-function relationship of various metal-iodosylarene complexes. In the present manuscript, density functional theoretical calculations were employed to investigate such relationship of a specific manganese-iodosylbenzene complex [MnIII(TBDAP)(PhIO)(OH)]2+ (1). Our results fit the experimental observations and revealed new mechanistic findings. 1 acts as a stepwise 1e+1e oxidant in sulfoxidation reactions. Surprisingly, C-H bond activation of 9,10-dihydroanthracene (DHA) by 1 proceeds via a novel ionic hydride transfer/proton transfer (HT/PT) mechanism. As a comparison to 1, the electrophilicity of an iodosylbenzene monomer PhIO was investigated. PhIO performs concerted 2e-oxidations both in sulfoxidation and C-H activation. Hydroxylation of DHA by PhIO was found to proceed via a novel ionic and concerted proton-transfer/hydroxyl-rebound mechanism involving 2e-oxidation to form a transient carbonium species.